Computational simulation of stent thrombosis induced by various degrees of stent malapposition - Qu, Zhuoran; Wei, Hongge; Du, Tianming; Qiao, Aike (Frontiers in Bioengineering and Biotechnology, 2022)
Percutaneous coronary intervention with stent implantation is one of the most commonly used approaches to treat coronary artery stenosis. Stent malapposition (SM) could increase the incidence of stent thrombosis but the quantitative association between SM distances and stent thrombosis is poorly clarified. The objective of this study was to determine the bio-mechanical reaction mechanisms underlying stent thrombosis induced by SM and to quantify the effect of various severity of SM on thrombosis. The thrombus simulation was performed in a continuous model based on the diffusion-convection response of blood substance transport. Simulated models included well-apposed stents and malapposed stents with various severity where the detachment distance ranges from 0 to 400μm. The abnormal shear stress induced by SM was considered as a critical contributor affecting stent thrombosis which was depended on changing different SM distances in the simulation. The results illustrated that the thrombus volume proportion was 1.88% with SM distance of 75μm(mild), 3.46% with 150μm and 3.93% with 400μm(severe), but a slight drop(3.18%) appeared at the detachment distance of 225μm(intermediate). The results indicate that when the SM distances are less than 150μm, the thrombus rises notably as the gap distances increase, whereas the growth trend of thrombogenicity weakens when it exceeds 150μm. So more attentions should be paid to the SM situation with a gap distance of 150μm. Moreover, when the stents have same length of SM, the thrombus tends to accumulate downstream to the distal end of the stent with the increasing SM distances.